Construction of Genomic DNA Library of Beijing Fatty Chick In lemda phage EMBL3 and Screen of Chick Heart Type Fatty Acid Binding Protein Gene - Ye, M.H.; Wen, J.; Cao, H.H.; Li, H.B.; Chen, J.L.; Zhao, G.P.; Zheng, M.Q. (International Journal of Poultry Science, 2007)
A genomic DNA library of Beijing Fatty chick was constructed in phage EMBL3 with a titer of 3.85×105. To testify the utility of this library we screened recombinant phages containing chick heart type fatty acid binding protein gene by Southern hybridization. In order to simplify the process of screen we determined sub-library which contained target gene firstly by PCR with specific primers. Several positive recombinants were detected. We selected one randomly to be digested with Sal I. Results showed inserted exogenous DNA was about 15Kb.